Healthcare providers infection prevention practices and associated factors in community clinics in Bangladesh: A cross-sectional study - Kamrul Hsan; Md. Saiful Islam; Md. Zohurul Islam; Nurullah Awal; David Gozal; Md. Marjad Mir Kameli; Mohammad Azizur Rahman; Md. Mahfuz Hossain (Public Library of Science (PLoS), 2022)
Healthcare associated infections impose serious challenges to safe and high-quality healthcare delivery, and have been closely associated with poor infection prevention practices. Infection prevention practices are poorly studied in Bangladesh, and no previous studies have examined these practices among healthcare providers of community clinics. The study aimed to assess infection prevention practices and associated factors among healthcare providers of community clinics in the rural area of Bangladesh. A cross-sectional study was conducted among 128 community healthcare providers in the Kurigram district of Bangladesh who were identified from 128 community clinics using a stratified random sampling technique. Data were collected between November and December, 2019 via face-to-face survey using a pre-tested semi-structured questionnaire. Only 37.5% community healthcare providers had adequate knowledge on infection prevention measures, and 39.1% had good infection prevention practices. Community healthcare providers with higher education were significantly more likely to have good infection prevention practices, and good infection prevention practices were associated with availability of hand washing facilities, and of soap in community clinic, and adequate knowledge of infection prevention. Implementation of an effective training program regarding infection prevention, along with adequate supply of infection prevention basic resources, and continuous monitoring and supervision are required to improve the currently faltering infection prevention knowledge and practices among community healthcare providers in Bangladesh.